Analisis Budaya Kerja dalam Meningkatkan Kinerja Karyawan pada CV Tirta Sasmita Pamulang - Noto Susanto; Asep Suherman; Widowati Widowati (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
This study examines the implementation of work culture in improving employee performance at CV Tirta Sasmita Pamulang. The research was conducted due to several workplace issues, including low employee discipline, lack of supervision, ineffective teamwork, and work practices that were not fully aligned with company procedures. The purpose of this study was to analyze the role of work culture in supporting employee performance within the company. A qualitative research method was applied using interviews, observations, and documentation as data collection techniques. The study involved four informants consisting of one key informant and three supporting informants. Data were analyzed descriptively through a SWOT analysis approach to identify the strengths, weaknesses, opportunities, and threats related to work culture and employee performance. The findings indicate that the implementation of work culture at CV Tirta Sasmita Pamulang has not been fully effective due to limited supervision, unequal employee skills, and limited human resources that result in double job responsibilities. However, teamwork and openness among employees have been relatively well established and contribute positively to maintaining work performance. Therefore, strengthening supervision and improving work discipline are necessary to enhance employee performance more effectively.